PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN ( Studi Pada Warung Makan Bakso Setan Di Semarang) - M. Fatoni Fajar M., 13.05.51.0161; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
This study aims to analyze the effect of product quality and price perception on customer satisfaction Bakso Setan Restaurant in Semarang. Location of this research was conducted at Bakso Setan Restaurant in Semarang. The population in this study were all buyers at Bakso Setan Restaurant. Population is not recorded and sampling using the Wibisono’s method. Research samples were 110 respondents. The sampling technique is done by using purposive sampling, which is a sample determination technique with certain considertations. The criteria used in sampling with purposive sampling methode are consumers who buy meatballs and eat on-site, who have at least high school education with age above 17 years. Data analyze method uses multiple regression. Analysis methode uses multiple linier regression with SPSS softwere. The results of the research are the same as the result of thr hypothesis. Product quality has a positve effect on customer satisfaction and price perception has a positive effect on customer satisfaction. The conclusion, if product quality is improved then customer satisfaction will incease and then perception of price is lowered, customer satisfaction will be better. of the first hypothesis testing show that partially (individuals) there is a positive and significant influence between Product Quality on Customer Satisfaction and partially (individuals) there is a positive and significant influence between Price Perception and Customer Satisfaction.